Increasing day three parasitaemia is observed after treatment of patients with artemether-lumefantrine and single dose of primaquine for uncomplicated Plasmodium falciparum malaria in Arbaminch Zuria district, Southwest Ethiopia - Bontu Abate; Bokretsion Gidey Brhane; Tsegahun Manyazewal; Hussien Mohammed; Yonas Wuletaw; Moges Kassa; Mesay Hailu; Getachew Tollera; Geremew Tasew; Ashenafi Assefa; Eyasu Makonnen (Malaria Journal)
Abstract Background Since 2017, the first-line treatment for uncomplicated Plasmodium falciparum infection in Ethiopia has been artemether-lumefantrine (AL), plus a single dose of primaquine (PQ). The World Health Organization (WHO) recommends regular monitoring of the first-line drug efficacy as crucial tool for supporting national treatment policies. This study aimed to assess the efficacy of AL with single dose of PQ for the treatment of uncomplicated P. falciparum malaria. Methods A prospective single-arm efficacy study was conducted among outpatients at Shecha Health Centre, aged six months and older with confirmed uncomplicated P. falciparum malaria from October 2023 to January 2024. Participants were treated with AL plus single dose of PQ and followed up to 28 days to evaluate clinical and parasitological responses. Kaplan–Meier (KM) survival analysis and per protocol (PP) analysis were used to estimate primary and secondary outcomes. Paired sample t-test was used to compare mean haemoglobin levels across follow-up dates (SPSS v.25). All comparisons were made at 95% confidence interval (CI), with a level of significance at 0.05. Results A total of 93 patients with uncomplicated P. falciparum were enrolled and 88 participants completed the study. Based on KM analysis the overall PCR uncorrected cure rate of AL plus single dose of PQ was 96.6% (95% CI 90.4–99.3%). The PCR-corrected cure rate was 100% (95% CI 95.8–100%). Despite high cure rate, accompanied by fast resolution of clinical symptoms, 17% of participants continued to have detectable parasitaemia on day 3. There was a slight decrease in mean haemoglobin on day 28 compared to the baseline. No serious adverse events were reported during the 28-day follow-up period. Conclusion The study findings reaffirm high efficacy of AL with a single dose of PQ for the treatment of uncomplicated P. falciparum malaria, with acceptable safety profile. These findings support the ongoing use of AL with a single dose of PQ as the primary treatment option for uncomplicated P. falciparum infections in the study area. In the context of the emergence and spread of partial artemisinin-based combination therapy(ACT) resistance in Africa, regular monitoring of the efficacy of current artemisinin-based combinations is recommended for the early detection of emerging drug resistance in the study setting and beyond.